Influence of Innovation Climate on Attraction and Retention of Human Capital Among Small and Medium Enterprises in Kenya - Olila, Mbadi; Maalu, Jackson; Muindi, Florence (Archives of Business Research, 2023)
Small and Medium Enterprises (SMEs) globally are currently operating in dynamic and uncertain business environments, making it necessary to attract and retain valuable human capital that can give them a competitive edge over peers. Most of these enterprises lack resource advantages and suffer from liabilities of size and newness, resulting in a big challenge in their attempts to compete favorably with large established firms. The ability of an enterprise to create and sustain a healthy and supportive innovation climate is consequential to its ability in attracting and retaining valuable human capital. This research aimed to ascertain the influence of innovation climate on attracting and retaining human capital among SMEs in Kenya. The top 100 SMEs for the year 2019 formed the study sample. A response rate of 59% was achieved. The study utilized structured questionnaires to collect data from founders of enterprises, and in their absence, the top management team was engaged. The data analysis methods used included SPSS and partial least squares structural equation modeling (PLS-SEM). This yielded results which established that various dimensions of innovation climate, including organizational support for innovation, organization structure, teamwork, leadership behaviour, and manager's approval, have a significant and positive influence on the attraction and retention of human capital among SMEs in Kenya. From these findings, it is recommended that founders and top management teams of SMEs should put in place a supportive and healthy innovation climate where human capital holders feel comfortable working and growing their careers in the long run. Such measures are instrumental in the attraction and retention of valuable human capital.